2021
DOI: 10.1007/s40831-021-00403-w
|View full text |Cite|
|
Sign up to set email alerts
|

Parameters Affecting the Precipitation of Al Phases from Aluminate Solutions of the Pedersen Process: The Effect of Carbonate Content

Abstract: Leaching experiments were performed in calcium aluminate slag with a high-sodium carbonate adaptation of the Pedersen process. A theoretical thermodynamic study of the pregnant leaching solution was conducted to specify the thermodynamically favored species that exist within. Using the HSC 9.0 software, a carbonation process simulation (neutralization of the aluminate solution with CO2 gas) was simulated. Laboratory carbonation experiments were conducted to verify the theoretical predictions. According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…3 and 4, this can perhaps be attributed to the precipitation and aging being conducted at elevated temperatures. A study [23] has shown that temperatures over 40 • C do favor dawsonite formation. In the case of test no.…”
Section: Precipitation Of Aluminum Tri-hydroxidementioning
confidence: 99%
See 2 more Smart Citations
“…3 and 4, this can perhaps be attributed to the precipitation and aging being conducted at elevated temperatures. A study [23] has shown that temperatures over 40 • C do favor dawsonite formation. In the case of test no.…”
Section: Precipitation Of Aluminum Tri-hydroxidementioning
confidence: 99%
“…The most notable outcomes from the ENSUREAL studies were the observations of the formation of a calcium-containing passivation layer around the slag grains, limiting the extraction of Al during leaching [21]. Further, leaching solutions with a Na 2 CO 3 concentration higher than 100 g/L were observed to promote dawsonite [NaAlCO 3 (OH) 2 ] precipitation over the desired Al tri-hydroxides gibbsite and bayerite [22][23][24]. Additionally, it was noted that the precipitation process had to be a combination of carbonation and aging (allowing the precipitate to sit in solution for at least 24 h after carbonation) to convert boehmite to bayerite and gibbsite [9,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al and Xiaobin et al found that sodium hydroxide promotes the growth of gibbsite and trihydrate aluminum hydroxide crystals. Marinos et al , discovered that high concentrations of sodium carbonate are conducive to the formation of sodalite aluminum hydroxide, and temperatures above 65 °C favor the direct precipitation of sodalite aluminum hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Further details on the process can be found in the available bibliographic sources [5][6][7]. Significant research has been conducted recently in the framework of the EnsureAl EU project for modernizing the Pedersen process [8][9][10][11][12][13][14][15]. As an example in our earlier work, the partial replacement of coke with charcoal was studied and it was found to ease the smelting process [16].…”
Section: Introductionmentioning
confidence: 99%